Functionality, muscular strength and cardiorespiratory capacity in the elderly: relationships between functional and physical tests according to sex and age - Toro-Román, Víctor; Ferrer-Ramos, Pau; Illera-Domínguez, Víctor; Pérez-Chirinos, Carla; Fernández-Valdés, Bruno (Frontiers in Physiology, 2024)
There are several tests that provide information about physical fitness and functionality in older adults. The aims of this study were: (i) to analyze the differences between sex and age in functional, strength and cardiorespiratory tests; and (ii) to study the correlations between functional, strength and cardiorespiratory tests according to sex and age. A total of 171 older adults (72.09 ± 13.27 kg; 1.59 ± 0.09 m; 72.72 ± 6.05 years) were divided according to sex (men: n=63; women: n=108) and age (≥60 <70: n=65; ≥70 <80: n=89; ≥80: n=18). Anthropometry, body composition, upper limb strength (hand grip; HG), lower limb strength (countermovement jump; CMJ), cardiorespiratory capacity (6 minutes walking test; 6MWT), timed up and go test (TUG) and Short Physical Performance Battery (SPPB) were assessed. Men showed higher values in CMJ height, HG and expired volume (VE) (p<0.05). There were no significant differences between sexes in TUG and SPPB. Regarding age, there were significant differences in CMJ, VE and maximum oxygen consumption (VO2max), TUG, gait speed, chair and stand test and SPPB total (p<0.05). The test times were higher in older people. Regarding correlations, the TUG showed significant correlations in all strength and cardiorespiratory tests, regardless of sex and age. The CMJ correlated more significantly with functional tests compared to HG. There were sex and age differences in functional, strength, and cardiorespiratory tests. The execution of quick and low-cost tests such as the CMJ and TUG could provide information on overall physical fitness in older adults.